An introduction to television studies - Bignell, Jonathan. (New York)
1 online resource (x, 344 pages)
Keywords: In this comprehensive textbook, now updated for its third edition, Jonathan Bignell provides students with a framework for understanding the key concepts and main approaches to Television Studies, including audience research, television history and broadcasting policy, and the analytical study of individual programmes. Features include: a glossary of key terms key terms defined in margins suggestions for further reading activities/assignments for use in class New and updated case studies fe.